PABPN1 functions as a downstream gene of CREB to inhibit the proliferation of preadipocytes - Xiao-Han Zhang; Jia-Xin Li; Xiao-Xu Wu; Qian Zhang; Ming Tian; Si-Qi Yang; Di Liu; Xiu-Qin Yang (Animal Bioscience)
Objective This study was conducted to reveal the role of nuclear poly(A) binding protein 1 (PABPN1) in the proliferation of preadipocytes, and to reveal the relationship between PABPN1 and cAMP response element (CRE)-binding protein (CREB) in the regulation of preadipocyte proliferation. Methods Vectors overexpressing and siRNAs against PABPN1/CREB were transiently transfected into both porcine preadipocytes and mouse 3T3-L1 cells. Preadipocyte proliferation was measured with cell counting kit-8, 5-ethynyl-2′-deoxyuridine, real-time quantitative polymerase chain reaction, Western blotting, and flow cytometry analyses. Additionally, the transcriptional regulation of CREB on PABPN1 were analyzed with dual-luciferase reporter gene and electrophoretic mobility shift assay. Results Overexpression of PABPN1 inhibits, and knockdown of PABPN1 promotes, the proliferation of both porcine preadipocytes and 3T3-L1 cell lines. PABPN1 overexpression increased, while knockdown decreased, the cell population in the G0/G1 phase. These indicates that PABPN1 repressed preadipocyte proliferation by inhibiting cell cycle progress. Additionally, it was revealed that CREB regulated the expression of PABPN1 through binding to the promoter and that CREB inhibited preadipocyte proliferation by repressed cell cycle progress. Furthermore, we showed that PABPN1 functions as a downstream gene of CREB to regulate the proliferation of preadipocytes. Conclusion PABPN1 inhibits preadipocyte proliferation by suppressing the cell cycle. We also found that CREB could promote PABPN1 expression by binding to a motif in the promoter. Further analysis confirmed that PABPN1 functions as a downstream gene of CREB to regulate the proliferation of preadipocytes. These results suggest that the CREB/PABPN1 axis plays a role in the regulation of preadipocyte proliferation, which will contribute to further revealing the mechanism of fat accumulation.